2007
DOI: 10.1007/s11892-007-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in people with diabetes and the metabolic syndrome: Pathophysiologic insights and therapeutic update

Abstract: Hypertension (HTN) and type 2 diabetes mellitus (T2DM) are emerging as epidemics of the 21st century and are important components of the metabolic syndrome (MS). Evidence demonstrates a relationship between HTN, T2DM, and several vascular and metabolic abnormalities that are components of the MS. HTN affects nearly 70 million Americans and over one billion worldwide; likewise, the MS affects 44% of the US population above the age of 60 years and is rapidly increasing. HTN associated with the MS has certain pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Evidence demonstrates a relationship between hypertension and type 2 diabetes mellitus, and several vascular and metabolic abnormalities [35]. Yugar-Toledo et al [36] found that patients with diabetes showed an increase in plasma nitrite/nitrate levels, suggesting an association with excessive production and/or inactivation of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrates a relationship between hypertension and type 2 diabetes mellitus, and several vascular and metabolic abnormalities [35]. Yugar-Toledo et al [36] found that patients with diabetes showed an increase in plasma nitrite/nitrate levels, suggesting an association with excessive production and/or inactivation of NO.…”
Section: Discussionmentioning
confidence: 99%
“…In complement of functional and molecular evidences for impairment of BK Ca channels in type-2 diabetic CASMCs, an experimental model was duplicated by feeding rats with high fat and glucose diet followed by injecting small dose STZ in the present study. This relatively new model is characterized by insulin resistance, hyperglycaemia, hyperlipidemia and moderate hypertension, which resembles the clinical manifestation of patients with typre-2 diabetes [22]. Therefore, the model is reliable and useful for investigating the underlying mechanisms of vascular dysfunction in typre-2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Non-insulin dependent diabetes mellitus is characterized by insulin resistance, altered glucose and fatty acid metabolism and moderate hypertension (Ganne et al, 2007;Kashyap and Defronzo, 2007). In many cases, it follows clinically apparent obesity (McGillis Bindler, 2007).…”
Section: Introductionmentioning
confidence: 99%